1999
DOI: 10.1161/01.cir.99.5.690
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurements of Infarct Size After Thrombolysis With a Necrosis-Avid MRI Contrast Agent

Abstract: Background-Gadophrin-2 is a new MRI contrast agent with high affinity for necrotic myocardium. The aim of the study was to evaluate whether noninvasive measurements of infarct size after thrombolysis are possible with gadophrin-2-enhanced MRI. Methods and Results-Coronary artery thrombosis was induced in 3 groups of dogs by the copper-coil technique.Thrombolytic therapy together with aspirin and heparin was initiated after 90 minutes of occlusion. One day (group A), 2 days (group B), or 6 days (group C) after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
1
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 27 publications
(26 reference statements)
1
63
1
2
Order By: Relevance
“…1,2 Although the quality of these images has improved, 3 discrepant reports continue to appear in the literature concerning their physiological interpretation. 4 -10 Data from our laboratory 5,6 and others 10 suggest that hyperenhanced myocardial regions observed after administration of extracellular MRI contrast agents such as Gd-DTPA are exclusively associated with irreversible ischemic injury, whereas results from other laboratories suggest a less specific 8 or even contrary 4,7,9 interpretation. These issues must be resolved before the full potential of contrast MRI can be recognized.…”
mentioning
confidence: 99%
“…1,2 Although the quality of these images has improved, 3 discrepant reports continue to appear in the literature concerning their physiological interpretation. 4 -10 Data from our laboratory 5,6 and others 10 suggest that hyperenhanced myocardial regions observed after administration of extracellular MRI contrast agents such as Gd-DTPA are exclusively associated with irreversible ischemic injury, whereas results from other laboratories suggest a less specific 8 or even contrary 4,7,9 interpretation. These issues must be resolved before the full potential of contrast MRI can be recognized.…”
mentioning
confidence: 99%
“…Mesoporphyrin provides accurate sizing of occlusive and reperfused infarctions. [17][18][19] The purpose of this study was (1) to characterize the peri-infarction zone in moderately injured myocardium by use of the combination of Gd-DTPA and mesoporphyrin MR contrast media and (2) to determine the function (wall thickening) of regions enhanced by Gd-DTPA and mesoporphyrin. The major hypothesis of this study is that the difference in the areas demarcated by the 2 agents is the salvageable border zone with reduced but residual contractile function.…”
mentioning
confidence: 99%
“…Therefore, extracellular contrast media may overestimate IS (12,13). On the other hand, it has been shown that the necrosis-specific MR contrast agent Gd-mesoporphyrin delineates only necrotic tissue and provides accurate measurement of IS (12)(13)(14)(15). This technique is less dependent on imaging time after Gd-mesoporphyrin injection due to persistent (24 hour) enhancement of acutely infarcted myocardium (13).…”
mentioning
confidence: 99%